Smallholders farmers defying global genetic erosion: documenting 60 years of peanut landrace conservation in a South American diversity center - Pérez, María Laura (2026)
Agricultural biodiversity is closely linked to human well-being. Concerns about the decline in crop diversity have been raised for over a century, although the extent and causes of these changes remain poorly understood. This study evaluated the diversity of peanut landraces conserved by smallholder farmers in the Guarani crop diversity center in South America over a 60–70 year period. Peanuts currently cultivated were collected and compared with accessions from the same region preserved in herbarium specimens. The results revealed that while many accessions are grouped under a few names, they exhibit significant phenotypic variability. Comparison between both collections revealed that most morphological types have been conserved. While the overall diversity was similar between the collections, changes in the composition and frequency of phenotypes managed by farmers were identified. Some landraces with extremely large or small seeds were absent in the modern collection, but hybrids, accessions from other diversity centers, and modern varieties were detected, increasing diversity. No trend toward replacing traditional varieties was observed, as the later are still preferred for self-consumption and low inputs requirements. The main ongoing evolutionary processes that sustain this genetic richness, were identified closely tied to local farming practices and social dynamics. While farmers in this center have successfully preserved peanut diversity, defying the expected landrace erosion, it is essential to implement equitable opportunities for these farmers and expand the use and commercialization of peanut landraces. Such efforts are crucial to ensure the long-term survival of the landraces as well as the evolutionary processes in a more sustainable environment.